Nudging study habits: A field experiment on peer tutoring in higher education. (February 2018) - Pugatch, Todd; Wilson, Nicholas
Highlights: We ran an experiment that advertised peer tutoring to college students. Receiving a one-time message increased tutoring attendance by 7 percentage points. Attendance at multiple tutoring sessions increased by 6 percentage points. Results are consistent with increased salience of tutoring to explain increased take-up. Results suggest that low-cost nudges can lead to important changes in study habits. Abstract: More than two of every five students who enroll in college fail to graduate within six years. Peer tutoring offers one approach to improve learning outcomes in higher education. We conducted a randomized controlled experiment designed to increase take-up of university tutoring services. Brief, one-time messages increased tutoring take-up by seven percentage points, or 23% of the control group mean. Attendance at multiple tutoring sessions increased by nearly the same amount, suggesting substantial changes in study habits in response to a simple and inexpensive intervention. The intervention cost $3.32–$14.58 per additional tutoring hour, the lowest reported in the literature on peer tutoring experiments. We find little evidence of advertising-induced tutoring on learning outcomes.